Religious moderation without context: critical analysis of Islamic Education textbooks junior high school in Indonesia - Saparudin, Saparudin; Emawati, Emawati (Atthulab: Islamic Religion Teaching and Learning Journal, 2023)
This study aims to analyze the value of religious moderation articulated in the textbooks on Islamic Education (PAI) and Morals for Junior High School. A qualitative approach was used using content analysis techniques which carried out by unitizing, sampling, recording/coding, reducing, abductively inferring, and narrating the samples. Furthermore, data validity was conducted through a focus group discussion technique involving experts in the field of moderation and teachers using textbooks. The results found that the content of religious moderation values has not been given proper space in PAI textbooks, although it is considered to be one of the gateways for the spread of radicalism in schools. This tendency is evidently seen in the following, first, the value of anti-violence being surpassed by normatively based dominance of personal morals and fiqh of worship. Second, national values are still neglected, meaning that the concept of islah and deliberation in the arguments cited for this theme has not been further elaborated. Third, the narrative of tolerance presented is very limited. Fourth, the description of local culture is almost forgotten. For example, the Walisongo's contextualization of local culture with Islam, has not been used to elaborate the value of moderation. Therefore, these findings indicate that there is an urgent need to strengthen the values of religious moderation in PAI textbooks used at Junior High School level in Indonesia. Â Studi ini bertujuan untuk menganalisis nilai moderasi beragama yang diartikulasikan dalam buku teks PAI dan Budi Pekerti SMP. Penelitian ini menggunakan pendekatan kualitatif dengan teknik content analysis terhadap buku teks yang digunakan di SMP. Tahapan analisis dilakukan melalui unitizing, sampling, recording/coding, reducing, abductively inferring, dan narrating. Keabsahan data dilakukan dengan teknik focus group discussion dengan melibatkan pakar bidang moderasi dan guru pengguna buku teks. Penelitian ini menemukan bahwa meski mengutip ayat-ayat al-QurÃ¡n yang relevan, namun muatan nilai-nilai moderasi beragama dalam buku teks PAI belum memperoleh ruang yang memadai, bahkan diasumsikan sebagai salah satu pintu masuk penyebaran paham radikal di sekolah. Kecenderungan ini nampak pada: pertama, nilai anti kekerasan terungguli oleh dominasi akhlak personal dan fikih ibadah yang dijelaskan secara normative; Kedua, nilai kebangsaan masih terabaikan. Konsep ishlah dan musyawarah dalam dalil yang dikutip untuk tema ini belum diperdalam penjelasannya; Ketiga, narasi toleransi disajikan sangat terbatas; dan keempat, deskripsi kebudayaan lokal nyaris terlupakan. Kontekstualisasi kebudayaan lokal dengan Islam yang dilakukan Walisongo misalnya tidak dimanfaatkan untuk mengelaborasi nilai moderasi. Implikasi penelitian menunjukkan adanya kebutuhan mendesak penguatan nilai-nilai moderasi beragama dalam buku-buku teks PAI yang digunakan pada tingkat SMP di Indonesia.Â